Problem-based learning influences on female students’ self-efficacy and critical thinking skills - Valenzuela, Tina Michelle (Kansas State University, 2022)
Gender inequalities continue into the 21st century and STEM was a major area of emphasis. Educators need to focus on female students to build their self-efficacy and critical thinking skills. The purpose of this study was to determine if problem-based learning (PBL) improves female elementary students’ self-efficacy and critical thinking skills. This case study based on Merriam examined how integrating PBL into the curriculum with STEM at the elementary level motivated female students towards selecting STEM careers while improving their self-efficacy and critical thinking skills. The PBL unit was developed to meet the NGSS Standards along with the Kansas Technology standards for students. The core idea of the unit was focused on shrinking our carbon footprint on the Earth with how humans and Earth interact together. A qualitative data analysis was conducted, and three themes were discussed during the findings stage. The analysis showed positive improvements for female students’ self-efficacy and critical thinking skills with problem-based learning infused with STEM. Butler’s feminist theory and Bandura’s self-efficacy theory were evident with female students as improvement was apparent during the PBL.
Keywords: Problem-based learning; STEM; Females; Self-efficacy